2022
DOI: 10.3389/fnana.2022.838567
|View full text |Cite
|
Sign up to set email alerts
|

Genoarchitecture of the Early Postmitotic Pretectum and the Role of Wnt Signaling in Shaping Pretectal Neurochemical Anatomy in Zebrafish

Abstract: The pretectum has a distinct nuclear arrangement and complex neurochemical anatomy. While previous genoarchitectural studies have described rostrocaudal and dorsoventral progenitor domains and subdomains in different species, the relationship between these early partitions and its later derivatives in the mature anatomy is less understood. The signals and transcription factors that control the establishment of pretectal anatomy are practically unknown. We investigated the possibility that some aspects of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Regarding overall brain development, there is general congruence in the description of expression patterns in the 28 hpf embryonic brain (Brożko et al., 2022; Lauter et al., 2013) compared to the 6 dpf larval brain dealt with in the present report. Moreover, for at least three genes studied in detail, it has been demonstrated that a general continuation of expression is seen between larval and adult brain ( islet1 : Baeuml et al., 2019; shha : Wullimann & Umeasalugo, 2020; otpa : Eugenin von Bernhardi et al., 2022).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Regarding overall brain development, there is general congruence in the description of expression patterns in the 28 hpf embryonic brain (Brożko et al., 2022; Lauter et al., 2013) compared to the 6 dpf larval brain dealt with in the present report. Moreover, for at least three genes studied in detail, it has been demonstrated that a general continuation of expression is seen between larval and adult brain ( islet1 : Baeuml et al., 2019; shha : Wullimann & Umeasalugo, 2020; otpa : Eugenin von Bernhardi et al., 2022).…”
Section: Discussionsupporting
confidence: 64%
“…However, a possible violation of the prosomeric model (Puelles & Rubenstein, 1993) is seen in the so-called tail end of various alar P2 domains that seemingly deviate posteriorly into P1 (e.g., gbx2 and lhx9; see Figure 5i). This observation has been made before (Brożko et al, 2022;Lauter et al, 2013) and may be interpreted in two ways: the tail end of these expression domains, which otherwise characterize alar P2, represents in fact cells that express these "dorsal thalamic" genes but are a part of P1. Alternatively, this tail end of alar P2 domains in question transgresses the P2/P1 boundary and forms truly a wedge of P2 between alar and basal P1.…”
Section: Distinct Combinations Of Gene Expression Domains Almost Perf...mentioning
confidence: 85%
“…The prosomeric model was used to localize the main common landmarks of the central nervous system during development, main partitions of the brain, and postulate homologies. Following the prosomeric model, the positions of neural populations can be identified by specific gene expression patterns (neural genoarchitecture) [41,42]. Homologues' derivatives share the same topological position in the Bauplan, an aspect that gene expression patterns help clarify [28,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Following the prosomeric model, the positions of neural populations can be identified by specific gene expression patterns (neural genoarchitecture) [41,42]. Homologues' derivatives share the same topological position in the Bauplan, an aspect that gene expression patterns help clarify [28,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Retinorecipient cells within the Pr, thalamus, and TeO cluster based on their unique gene expression profiles that do not appear to change with loss of retinal input (Sherman et al, 2021). These findings and others suggest that genetic profiles are hard-wired in regions where RGC axons make connections and govern cellular mechanisms for the development and function of AFs (Baier, 2013;Brożko et al, 2022;Sherman et al, 2021). Due to identified changes in neuronal identity in the gsx1 mutant Pr, we looked to next assess the morphology of incoming RGC axons using Tg(atoh7:eGFP), a transgenic line that demarcates all RGCs and their axons with GFP expression (Poggi et al, 2005).…”
Section: Pretectal Af7 Is Predominantly Disrupted In Gsx1 Mutantsmentioning
confidence: 88%